Influenza and respiratory syncytial virus during the COVID‐19 pandemic: Time for a new paradigm? - Binns, Emma; Koenraads, Marianne; Hristeva, Lidia; Flamant, Alix; Baier‐Grabner, Sebastian; Loi, Mervin; Lempainen, Johanna; Osterheld, Elise; Ramly, Bazlin; Chakakala‐Chaziya, Jessica; Enaganthi, Niveditha; Simó Nebot, Silvia; et al. (Pediatric pulmonology, 2022)
Seasonal epidemics of influenza and the respiratory syncytial virus (RSV) are the cause of substantial morbidity and mortality among children. During the global coronavirus disease 2019 (COVID‐19) pandemic, the epidemiology of these viruses seems to have changed dramatically. In Australia and New Zealand, a significant decrease in both influenza and bronchiolitis have been noticed during usual peak seasons. Data from early months of winter seasons in Europe are showing similar trends. This current scenario imposes a reconsideration of the paradigm that toddlers and young schoolchildren are the main drivers of seasonal RSV outbreaks and respiratory epidemics in general. In this article, we summarize current literature, address current knowledge or role of adults in the RSV epidemiology, describe the lessons learned from pertussis epidemics and call the international community to better understand the community transmission dynamics of respiratory infections in all age groups. This can allow the establishment of better and more affordable preventive measures in the whole population level, which can ultimately save millions of child lives.